Himachal Pradesh Second Five year Plan 1956-61 (Hosuing Development Scheme) - Planning Commission (Planning Commission, 1956)
Under priority I only 7.82 lacs have been allotted to this state. It is, therefore, proposed to construct 150 houses under subsidized Industrial housing Scheme, and 100 houses under Special housing and urban land development schemes. These targets will be achieved within the first two years of the plan.
Himachal Pradesh Government